Fit-Tested N95 Masks Combined With Portable High-Efficiency Particulate Air Filtration Can Protect Against High Aerosolized Viral Loads Over Prolonged Periods at Close Range. (10th May 2022) - Landry, Shane A; Subedi, Dinesh; Barr, Jeremy J; MacDonald, Martin I; Dix, Samantha; Kutey, Donna M; Mansfield, Darren; Hamilton, Garun S; Edwards, Bradley A; Joosten, Simon A
Abstract: Background: Healthcare workers (HCWs) are at risk from aerosol transmission of severe acute respiratory syndrome coronavirus 2. The aims of this study were to (1) quantify the protection provided by masks (surgical, fit-testFAILED N95, fit-testPASSED N95) and personal protective equipment (PPE), and (2) determine if a portable high-efficiency particulate air (HEPA) filter can enhance the benefit of PPE. Methods: Virus aerosol exposure experiments using bacteriophage PhiX174 were performed. An HCW wearing PPE (mask, gloves, gown, face shield) was exposed to nebulized viruses (10 8 copies/mL) for 40 minutes in a sealed clinical room. Virus exposure was quantified via skin swabs applied to the face, nostrils, forearms, neck, and forehead. Experiments were repeated with a HEPA filter (13.4 volume-filtrations/hour). Results: Significant virus counts were detected on the face while the participants were wearing either surgical or N95 masks. Only the fit-testPASSED N95 resulted in lower virus counts compared to control ( P  = .007). Nasal swabs demonstrated high virus exposure, which was not mitigated by the surgical/fit-testFAILED N95 masks, although there was a trend for the fit-testPASSED N95 mask to reduce virus counts ( P  = .058). HEPA filtration reduced virus to near-zero levels when combined with fit-testPASSED N95 mask, gloves, gown, and face shield. Conclusions: N95 masks that have passed a quantitative fit-test combined with HEPA filtration protects against high virus aerosol loads at close range and for prolonged periods of time. Abstract : Only a fit-tested N95 mask provided protection against virus aerosol; surgical masks and non-fit-tested N95 masks were not superior to no-mask control. The combination of air purification and fitted N95 mask provided protection against very high virus aerosol load.